Electronic prescription as contributing factor for hospitalized patients' safety - Gimenes, Fernanda Raphael Escobar (2006)
The following study was performed to identify factors related to medication errors in the computerized physician order entry and their advantages and disadvantages according to doctors, nursing team and administrative officers. It is a survey descriptive study carried out at three units of a Brazilian academic hospital in the southeast area. The study was divided in two phases. In the first phase, we analyzed a total of 1,349 prescriptions from general medical unit, surgical and orthopaedic wards during 30 days consecutively. A semi-structured instrument, elaborated by a group of researchers for the study proposals, was used. In the second phase, a semi-structured questionnaire was applied to the health professionals containing closed and open items approaching their opinion about the composition of electronic prescription, the advantages and disadvantages of them, and their suggestions for its improvement. Out of 1,349 prescriptions observed, 17.5% presented deletions, 25.0% medicines written manually and 17.0% of them were incomplete. Some of the advantages pointed by health professionals were its legibility (37.5%), little time spent when elaborating and emitting them (20.5%) and the way they are a practical and organized (8%). The disadvantages pointed were repetition of previous prescriptions (34%), typing mistakes (17%), dependence on computers (11%) and alterations made manually (7%). We conclude, this way, that the computerized prescription order entry represents a great progress among the strategies used to minimize medication errors caused by prescriptions badly formulated. However, it doesn't eradicate the possibility of medication error occurrences, needing some system modifications. _________________________________________________________________________________________________________ RESUMEN